Criterion validity of ultrasound in the identification of calcium pyrophosphate crystal deposits at the knee: an OMERACT ultrasound study. Issue 2 (28th September 2020) - Filippou, Georgios; Scanu, Anna; Adinolfi, Antonella; Toscano, Carmela; Gambera, Dario; Largo, Raquel; Naredo, Esperanza; Calvo, Emilio; Herrero-Beaumont, Gabriel; Zufferey, Pascal; Bonjour, Christel Madelaine; MacCarter, Daryl K; et al.
Abstract : Objective: To evaluate the discriminatory ability of ultrasound in calcium pyrophosphate deposition disease (CPPD), using microscopic analysis of menisci and knee hyaline cartilage (HC) as reference standard. Methods: Consecutive patients scheduled for knee replacement surgery, due to osteoarthritis (OA), were enrolled. Each patient underwent ultrasound examination of the menisci and HC of the knee, scoring each site for presence/absence of CPPD. Ultrasound signs of inflammation (effusion, synovial proliferation and power Doppler) were assessed semiquantitatively (0–3). The menisci and condyles, retrieved during surgery, were examined microscopically by optical light microscopy and by compensated polarised microscopy. CPPs were scored as present/absent in six different samples from the surface and from the internal part of menisci and cartilage. Ultrasound and microscopic analysis were performed by different operators, blinded to each other's findings. Results: 11 researchers from seven countries participated in the study. Of 101 enrolled patients, 68 were included in the analysis. In 38 patients, the surgical specimens were insufficient. The overall diagnostic accuracy of ultrasound for CPPD was of 75%—sensitivity of 91% (range 71%–87% in single sites) and specificity of 59% (range 68%–92%). The best sensitivity and specificity were obtained by assessing in combination by ultrasound the medial meniscus and the medial condyle HC (88% and 76%, respectively). No differences were found between patients with and without CPPD regarding ultrasound signs of inflammation. Conclusion: Ultrasound demonstrated to be an accurate tool for discriminating CPPD. No differences were found between patents with OA alone and CPPD plus OA regarding inflammation.